2023
DOI: 10.3389/ffgc.2022.1084480
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling and allocation patterns: Implications for predicting productivity across plant communities

Abstract: As the application of allometry continues to expand, the variability in the allometry exponent has generated a great deal of debate in forest ecology. Some studies have reported counterintuitive values of the exponent, but the sources of such values have remained both unexplored and unexplained. Therefore, the objectives of our analyses were to: (1) uncover the global patterns of allometric variation in stem height with stem diameter, crown radius with stem diameter or stem height, crown depth with stem diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Some models are grounded in sound theory, while others are purely empirical. The power law function is the most common model, based on many theoretical arguments [14]. Mehtatalo and Lappi [57] suggested that flexibility and parsimony (i.e., combining simplicity with high predictive or explanatory power) should be considered in addition to the parameter's obvious biological interpretability when choosing the best function.…”
Section: Statistical Analysis 241 Base Model Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some models are grounded in sound theory, while others are purely empirical. The power law function is the most common model, based on many theoretical arguments [14]. Mehtatalo and Lappi [57] suggested that flexibility and parsimony (i.e., combining simplicity with high predictive or explanatory power) should be considered in addition to the parameter's obvious biological interpretability when choosing the best function.…”
Section: Statistical Analysis 241 Base Model Selectionmentioning
confidence: 99%
“…Earlier studies suggested that height-diameter relationships vary among tree species, stands, and geographic regions [10][11][12][13]. However, recent evidence indicates that much of the variability arises from measurement errors, sampling biases, and failure to capture the diameter size distribution [14]. They found out that plants exhibit a striking similarity in allometry across taxonomic lineages, climate zones, biomes, and disturbance regimes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are grounded in sound theory, while others are purely empirical in nature. The power law function is the most common one based on a number of theoretical arguments (SILESHI; NATH; KUYAH, 2023). MEHTATALO e LAPPI (2020)…”
Section: Base Model Selectionmentioning
confidence: 99%